The Dutch Disease in Reverse: Iceland's Natural Experiment - Thorvaldur Gylfason; Gylfi Zoega (Center for Economic Studies and ifo Institute (CESifo), 2017)
For a long time, abundant natural resources brought Iceland a high and volatile real exchange rate with adverse effects on manufacturing and services. During 2003-2008, another national treasure, the sovereign's AAA rating, was used by privatized banks to attract foreign capital, elevating the real exchange rate even further. The financial collapse and the associated collapse of the currency in 2008 left the country with a large foreign debt which offset some of the effect of the natural resources on the real exchange rate. In effect, this was the Dutch disease in reverse as witnessed, in particular, by a massive increase in the number of tourists following the financial collapse. This paper discusses the behavior of the exchange rate of the Icelandic króna before and after 2008 as well as its relationship to natural resources, capital flows, output, exports and imports, including tourism.
Keywords: F41; O23; O33; 330; natural resource curse; Dutch disease; financial crisis